Signed, Sealed, and Delivered with Trust: Non-Resident Citizens’ Experiences of Newly Adopted Postal Voting - Wass, Hanna; Peltoniemi, Johanna; Weide, Marjukka; Nemčok, Miroslav (Frontiers in Political Science, 2021)
The COVID-19 pandemic has made it clear that the traditional “booth, ballot, and pen” model of voting may not be feasible during a health crisis. It has highlighted the need to assess whether existing electoral legislations include enough instruments to ensure citizens’ safety when voting. Such instruments, often grouped under the umbrella of voter facilitation or convenience voting, range from voting in advance and absentee voting to assisted voting and voting at home and in institutions. While most democracies have implemented at least some form of voter facilitation, substantial cross-country differences exist. In the push to develop pandemic-sustainable elections in different contexts, variation in voter facilitation makes it possible to learn from country-specific experiences. In this study, we focus on Finland, where the municipal elections were postponed from April to June 2021. Although the decision was mostly justified by the increase in COVID-19 cases, the position of the quarantined eligible voters was also considered. The failure to organize health-safe voting in the original schedule emphasizes a paradox in the Finnish legislation: caution in introducing new facilitation instruments has led to lower levels of preparedness and flexibility. A forerunner in implementing advance voting, Finland has only recently introduced postal voting, restricted to voters abroad. Hence, we ask: what can be learned from it if expanded to all voters to enhance the sustainability of elections in future crises like pandemics? Our analyses are based on a survey conducted among non-resident voters (n = 2,100) after the 2019 parliamentary elections in which postal voting from abroad was introduced. Our results show that whereas trust in the integrity of postal voting is quite high, various efforts needed from individual voters substantially increase the costs of postal voting. Postal operations also raise concerns. Voters felt that requiring witnesses made postal voting cumbersome, an issue that needs resolving, particularly if applying postal voting in a pandemic context. The Finnish case constitutes a concrete example of a situation in which voter facilitation targeted to a particular segment of society may become a testbed for electoral engineering (see Norris 2004) that will improve voting opportunities for everyone.